THE DEVELOPMENT OF MODERN THEOLOGY - Abdul Wahab Syakhrani; Ahmad Zaini (ADISAM Publisher, 2022)
This modern age is also the spirit of the new age that existed in the 19th century. As a form of civilization and the spirit of the times, modernity is characterized by 3 things, namely individualism, rationalism and progress. Therefore, modern technology is able to compete in the current era of technological development.